Speech Analysis in Legal Proceedings: Urgent Needs, Problems and Ways to Solve Them - E. I. Galyashina (Теория и практика судебной экспертизы)
The article describes the problems in legal proceedings that impede effective use of special knowledge of speech necessary to qualify offenses committed by means of speech actions. Among them the imperfection of the current legislation on forensic expert activity is mentioned, where there are no uniform professional qualifications and requirements for state forensic experts and persons who are not the employees of state forensic institutions and who are quite often involved in the conduct of linguistic expertise, authorship and phonogram examinations. It is stated that due to the lack of professional training in forensic specialties of such non-state experts, the quality of their speech analysis does not meet the need of the legal community and civil society in objective and effective examinations, the results of which could be used in trial. If the incompetence of non-state experts is revealed, their opinions are recognized as an inadmissible evidence, reexaminations are assigned to the state forensic institutions, which significantly delays the proceedings. It is proposed to legislate the mandatory certification for nonstate experts, to unify the procedure of additional professional education in the field of specific expert’s specialties for state and non-state forensic experts. In order to solve the problems mentioned above it is proposed to develop and implement a passport for each forensic specialty, a single nomenclature of forensic specialties corresponding to the types of forensic speech examinations, to unify additional professional retraining and professional development programs.